Технология проведения маркетингового исследования на региональном рынке труда - Игошин, М. М. (Культура народов Причерноморья, 2014)
В статье рассмотрены теоретические вопросы технологи маркетинговых исследований регионального рынка труда. Дано определение маркетинга регионального рынка труда. Представлены основные цели маркетинга рынка труда. Рассмотрены концептуальные направления исследования рынка труда. Представлены перспективные направления маркетинговых исследований рынка рабочих мест и рынка рабочей силы АР Крым. У статті розглянуто теоретичні питання технологи маркетингових досліджень регіонального ринку праці. Дано визначення маркетингу регіонального ринку праці. Представлені основні цілі маркетингу ринку праці. Розглянуто концептуальні напрями дослідження ринку праці. Представлені перспективні напрямки маркетингових досліджень ринку робочих місць і ринку робочої сили АР Крим. Conditions for the successful supply and demand management in labor market need the use of marketing methodology. Marketing labor involves the creation and operation of an integrated system of effective regulation of social and labor relations, providing maximum employment, stimulate employment, the definition of the real cost of labor. Enormous practical importance of marketing research as one of the management determines the relevance of the research that concerns the development of a regional labor market. The paper presents an analysis of the publications of domestic and foreign scientists who conducted the research in this field of science. In particular, the research works by Beljaevsky I.K., Durovich A.P. Sarukhanov E.E., Sotnikova S.I., Tomilova V.V., Semerkova L.N. and others are analyzed . The paper presents the process of market research of regional labor market as a management model that is constructed logically consistent process, the main structural elements of which . The main conclusions of the paper are well structured and scientificallybased.